2021
DOI: 10.1021/acs.jpclett.0c03395
|View full text |Cite
|
Sign up to set email alerts
|

Single Gold Bipyramid Nanoparticle Orientation Measured by Plasmon-Resonant Scattering Polarimetry

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, we also point out that the errors increase with the Θ 𝑓𝑖𝑡 . Indeed, at every collection NA, the degree of polarization is nearly the same for any orientation in the range 80-90 ° [28]. In other words, the measurement is less sensitive when the nanoparticles are nearly positioned parallel to the substrate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, we also point out that the errors increase with the Θ 𝑓𝑖𝑡 . Indeed, at every collection NA, the degree of polarization is nearly the same for any orientation in the range 80-90 ° [28]. In other words, the measurement is less sensitive when the nanoparticles are nearly positioned parallel to the substrate.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, in a previous publication, we have demonstrated that the polarimetric measurement of 3D orientation strongly depends on the NA of the collection objective by experimentally measuring the δ at different NA [28]. In fact, from the dependence of δ(NA), the out -of -plane angle Θ can also be determined with a higher certainty in defining the dipolar nature.…”
Section: Introductionmentioning
confidence: 99%
“…19,25−27 A widespread variant used polarized Fourier imaging to distinguish in-plane and out-of-plane dipole contributions. 7,8,[12][13][14]28 Various other protocols have been introduced, such as separating different emission directions with an annular plate, 29 comparing degrees of polarization with different collection apertures, 30 using imaging aberrations, 26,31 probing the effect of a nearby interface on decay dynamics, 5,32 and separating spectrally the electric and magnetic contributions. 33 All of these methods rely on comparing the measured observable (degree of polarization, Fourier image, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been proposed to probe the number and orientation of radiating dipoles in nanoemitters. A first range of methods used polarimetric analysis of the luminescence, either by decomposition into several polarization components , or by using a rotating polarizer to measure the degree of polarization. ,, A second class of methods uses the radiation pattern (angular distribution of the emission) measured by Fourier (back focal plane) imaging ,,, or indirectly by defocused imaging. , A widespread variant used polarized Fourier imaging to distinguish in-plane and out-of-plane dipole contributions. ,, , Various other protocols have been introduced, such as separating different emission directions with an annular plate, comparing degrees of polarization with different collection apertures, using imaging aberrations, , probing the effect of a nearby interface on decay dynamics, , and separating spectrally the electric and magnetic contributions …”
Section: Introductionmentioning
confidence: 99%